2020
DOI: 10.26504/rs112
|View full text |Cite
|
Sign up to set email alerts
|

Talking about sex and sexual behaviour of young people in Ireland

Abstract: Research from a joint ESRI/HSE Health and Wellbeing research programme analyses how young people receive information on sex and relationships. Using data from the Growing up in Ireland ’98 Cohort at 13 and 17 years of age, the research also examines the role of this information in shaping sexual behaviours among Irish adolescents. The research finds that four in ten 17 year-olds have not spoken to their parents about sex and relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…and age verificaYon (Children's Commissioner, 2023), although a review of qualitaYve research with young people noted that efforts to prevent young people from accessing pornography, such as through idenYty screening and blocking websites by parents and schools, were not viewed as deterrents and were easily overcome when desired (Peterson et al, 2023). However, in this report, parental While the analyses in this report found little association between the timing of RSE receipt, the timing of discussions with parents about sex and relationships, or the types of topics discussed with parents, and use of pornography, previous research using GUI has highlighted the fact that the measure of RSE receipt (and parental discussions) does not capture important dimensions of formal and informal sex education including quality and quantity (Nolan and Smyth, 2020). In general, previous research focuses on the negaYve aspects of pornography use, but some research notes that, in certain circumstances, pornography can provide useful informaYon about sex (Litsou et al, 2021).…”
Section: Implications For Policy and Practicecontrasting
confidence: 63%
See 4 more Smart Citations
“…and age verificaYon (Children's Commissioner, 2023), although a review of qualitaYve research with young people noted that efforts to prevent young people from accessing pornography, such as through idenYty screening and blocking websites by parents and schools, were not viewed as deterrents and were easily overcome when desired (Peterson et al, 2023). However, in this report, parental While the analyses in this report found little association between the timing of RSE receipt, the timing of discussions with parents about sex and relationships, or the types of topics discussed with parents, and use of pornography, previous research using GUI has highlighted the fact that the measure of RSE receipt (and parental discussions) does not capture important dimensions of formal and informal sex education including quality and quantity (Nolan and Smyth, 2020). In general, previous research focuses on the negaYve aspects of pornography use, but some research notes that, in certain circumstances, pornography can provide useful informaYon about sex (Litsou et al, 2021).…”
Section: Implications For Policy and Practicecontrasting
confidence: 63%
“…As previous research had indicated some relaYonship between pornography use and early pubertal Yming, we disYnguish between females who had early periods (11 or younger) and others, and between males whose voices had fully or parYally broken at age 13 and others. Males and females differ significantly in their sources of informaYon on sex and on the Yming of parental discussions of sex, with a higher proporYon of men reporYng their parents had never talked to them about sex (38 per cent compared with 25 per cent) (Nolan and Smyth, 2020). Parents were also asked about whether they had talked to their children about five different issues: sex and sexual intercourse;…”
Section: Data and Methods | 21mentioning
confidence: 99%
See 3 more Smart Citations